Active post-operative phoned search for late infections of surgical site and thromboembolic events in the late postoperative period of plastic surgeries in a day hospital in the municipality of Porto Alegre - Nicoletti, Diana Rodrigues; de Oliveira, Dionísia Oliveira; Cioato, Stefânia Giotti; Fernandes, Morgana Thais Carollo (Clinical and Biomedical Research, 2018)
Introduction: Elective and plastic surgical procedures are normally considered safer than emergency surgeries, although they cause concern to health services. The aim of this study was to analyze the active phoned search as a screening instrument for the diagnosis of surgical site infection (SSI) and thromboembolic events (TEs) in the late postoperative care of plastic surgeries in a private day hospital in the city of Porto Alegre. Methods: Quantitative, descriptive, retrospective, cross-sectional study. Data was collected from a database provided by phoned active search of sign and symptoms for epidemiological monitoring by the control infection service of a day-hospital, from July 2015 to February 2017. Results: A total of 3.595 patients were effective contacted in the indicated period. Among these patients, 77.6% received guidance on TEs. Moreover, 0.4% and 0.2% of patients reported signs and symptoms of SSI and TE, respectively. Associated procedures caused 50.0% of SSIs and 87.5% of TEs. Phoned search increased in 0.2% the number of reported cases of both adverse events in the overall sample. Conclusion: SSI and TE are worrying events for health institutions, since they can put patient safety at risk. Therefore, the data obtained in this study were used as a basis to qualify phoned search as an effective screening instrument for SSI and TE and provided support for the development of more consistent phoned search mechanisms for monitoring these postoperative events. Keywords: Epidemiological surveillance; infections; thromboembolism; plastic surgery